Restoring global offset and lower limb length with a 3 offset option double-tapered stem - Stefano Biggi; Lorenzo Banci; Riccardo Tedino; Andrea Capuzzo; Gabriele Cattaneo; Stefano Tornago; Andrea Camera (BMC Musculoskeletal Disorders, 2020)
Abstract Background A proper restoration of hip biomechanics is fundamental to achieve satisfactory outcomes after total hip arthroplasty (THA). A global hip offset (GO) postoperatively reduction of more than 5 mm was known to impair hip functionality after THA. This study aimed to verify the restoration of the GO radiographic parameter after primary THA by the use of a cementless femoral stem available in three different offset options without length changing. Methods From a consecutive series of 201 patients (201 hips) underwent primary cementless THA in our center with a minimum 3-year follow up, 80 patients (80 hips) were available for complete radiographic evaluation for GO and limb length (LL) and clinical evaluation with Harris hip score (HHS). All patients received the same femoral stem with three different offset options (option A with – 5 mm offset, option B and option C with + 5 mm offset, constant for each sizes) without changing stem length. Results Mean GO significantly increased by + 3 mm (P < 0.05) and mean LL significantly decreased by + 5 mm (P < 0.05) after surgery, meaning that postoperatively the limb length of the operated side increased by + 5 mm. HHS significantly improved from 56.3 points preoperatively to 95.8 postoperatively (P < 0.001). Offset option A was used in 1 hip (1%), B in 59 hips (74%) and C in 20 hips (25%). Conclusions The femur is lateralized with a mean of + 5 mm after surgery than, the native anatomy, whatever type of stem was used. Thus, the use of this 3-offset options femoral stem is effective in restoring the native biomechanical hip parameters as GO, even if 2 offset options were considered sufficient to restore GO.